The invisible leader: Facilitation in Lesson Study - John Paul Mynott, Daryl Michel (Educational Process: International Journal)
Background/purpose – Developing the body of knowledge about how facilitators act and engage with participants is essential to developing Lesson Study (LS) facilitation. This research reveals how two LS facilitators from the United Kingdom and the United States support and lead cycles.